Sentence Processing Difficulties in Academic English: A Psycholinguistic Study of EFL Students - Ulysa Humayrah; Novita Ritonga; Afia Nur Meiza; Yani Lubis (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates sentence processing difficulties in academic English from a psycholinguistic perspective, focusing on EFL university students. The research aims to identify how learners plan, parse, and interpret complex academic sentences during real-time reading. A qualitative approach was employed to capture cognitive processes underlying comprehension. Data were collected through academic reading tasks, think-aloud protocols, interviews, and stimulated recall sessions. The findings reveal that learners face persistent difficulties when processing syntactically complex sentences, long noun phrases, and multi-clause structures. These difficulties are closely linked to limited working memory capacity, low processing automaticity, and heavy reliance on word-by-word translation strategies. Learners often experience cognitive overload, which leads to slow reading, frequent rereading, and inaccurate interpretation of grammatical relationships. Emotional factors such as anxiety and lack of confidence also interact with cognitive load and further disrupt comprehension. The study concludes that sentence processing problems in academic English are rooted in psycholinguistic constraints rather than insufficient linguistic knowledge. The findings emphasize the need for instructional approaches that focus on improving processing efficiency, syntactic integration, and automaticity in EFL academic reading contexts.